The New Breed of Trade Marks: Sounds, Smells and Tastes - McGrath, Jacey K (Victoria University of Wellington Law Review, 2001)
Sounds, smells and tastes can now be registered as trade marks in New Zealand under the Trade Marks Act 1953. These novel types of signs raise concerns about their ability to act as effectively as the more traditional word and design trade marks. Consumers will have to utilise less perceptive senses in order to comprehend these marks, and may not be able to rely on them to distinguish products at the point of sale. The inherent intangibility of these marks may also have implications for determining questions of similarity and the likelihood of confusion in infringement actions. Unlike the more traditional trade marks, sounds, smells and tastes are usually intrinsic features of products. Such characteristics should not be registrable as trade marks because they are not sufficiently separate from the underlying goods and would allow a trader to have a monopoly over their production. The rationale behind trade mark protection must not be lost sight of in the desire to shield innovative traders who utilise exciting signs to market their products.